1999
DOI: 10.1111/j.1151-2916.1999.tb01724.x
|View full text |Cite
|
Sign up to set email alerts
|

Evolution in Structural and Optical Properties of Stannic Oxide Xerogel upon Heat Treatment

Abstract: Upon consecutive heat treatments at increasing temperatures, the microstructure of solution-sol-gel-derived stannic oxide (SnO 2 ) xerogel evolves in three stages: (I) below 300°C, characterized by extensive dehydroxylation and gel shrinkage with little grain growth and surface loss; (II) between 300°and 500°C, by extensive crystallization, leading to dramatic surface loss (by 70%); and (III) above 500°C, by grain growth. Concurrently, the UV-absorption edge shows red shifts during stages I and II and blue shi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 30 publications
1
28
0
Order By: Relevance
“…The spectra is dominated by the broad bands associated with surface related disorder. 12 Superposed are observed the peaks associated to the cassiterite structure, which are identified when compared with those of the reference tin oxide. A slight shift of the A1g peak, centered at around 638 cm…”
Section: Resultsmentioning
confidence: 99%
“…The spectra is dominated by the broad bands associated with surface related disorder. 12 Superposed are observed the peaks associated to the cassiterite structure, which are identified when compared with those of the reference tin oxide. A slight shift of the A1g peak, centered at around 638 cm…”
Section: Resultsmentioning
confidence: 99%
“…Compared with the fast nucleation and aggregation growth in a supersaturated aqueous solution, the slow nucleation process guaranteed a low concentration of the solution and reduced the collision times of subunits in our experimental conditions, thus giving the subunits enough time to aggregate on the c axis according with the polarity of the ZnO crystal. In the aggregation process, water played the important role as a binder to control nanocrystal aggregation because the surface hydroxyls are the main reason for the aggregation of metal oxide nanoparticles [36,37]. However, with increasing aggregation time and coarsening secondary particles, to ensure the lowest energy of the system, one end of the aggregation particles spreads and the radian of the profile becomes round.…”
Section: The Transformation Process and Formation Mechanism Of Zno Prmentioning
confidence: 99%
“…Therefore, the structure of the products could be well tuned by controlling the ratio of wate to alcohol. As for the possible formation mechanism of the selfassembly microstructures, it was reported that surface hydroxyls were the main reason for the aggregation of metal oxide nanoparticles, because water acted as a binder to control the nanocrystal aggregation [17]. The ZnO products synthesized at a higher NaOH concentration in our case and it can be speculated that there were hydroxyls on the surface of the products and therefore they can aggregate by interaction with hydroxyls of solvents during the reaction process.…”
Section: Resultsmentioning
confidence: 91%